The effects of carbon emissions and agency costs on firm performance - Muhammad Nurul Houqe; Solomon Opare; Muhammad Kaleem Zahir-ul-Hassan; Kamran Ahmed (Journal of Risk and Financial Management, 2022)
Carbon emissions and agency costs can have an impact on firms' financial performance. However, limited attention has been paid to the combined and gradual effects of these two factors on firms' performance. We explore the separate and combined effects of carbon emissions and agency costs on firms' financial performance by utilizing data from 2323 US firms that disclosed their environmental information to CDP from 2007 to 2016. The results indicate that firms with higher carbon emissions experience lower performance as the market reacts negatively. Further, firms with both higher carbon emissions and higher agency costs have lower performance. We also investigated year-on-year change in firm performance and found that, keeping agency costs constant, a change in carbon emissions leads to lower performance. Overall, the findings suggest that when the market responds negatively to firms' environmental decisions, high agency costs exacerbate the adverse effect of high carbon emissions on firm performance.
Keywords: 330; agency costs; carbon emissions; firm performance; CDP